Training on Silage Production Using Kinggrass Forage and Rice Straw to Improve the Availability of Feed for Ruminant Livestock in Wangka Village - Salvius Edwintus Tenga Wona; German Yohanes Sola; Yohanes Freadyanus Kasi (Samakta: Jurnal Pengabdian Kepada Masyarakat, 2026)
Feed availability is one of the key factors determining the success of ruminant livestock operations, especially during the dry season when forage becomes increasingly scarce. This community service activity aims to improve farmers’ knowledge and skills in processing kinggrass and rice straw into silage as a high-quality alternative feed with a longer shelf life. The activity was conducted in Wangka Village on May 8, 2026, using the Participatory Action Research (PAR) approach through the following stages: problem identification, extension, demonstration, hands-on silage production, mentoring, and activity evaluation. The evaluation was conducted through observation of participants’ ability to practice each stage of silage production, interviews, and assessment of the physical quality of the resulting silage. The results of the community service activity showed that participants were able to understand and practice the silage-making process, starting from chopping forage, mixing fermentation ingredients, compacting the mixture in an airtight container, to the fermentation process itself. The resulting silage had good physical quality, characterized by a greenish-brown color, a fresh, sour aroma, a soft texture, and the absence of mold, indicating that the fermentation process occurred optimally. In addition to improving participants’ skills in feed processing, this activity also enhances the community’s understanding of the importance of silage technology as a solution for securing feed reserves during the dry season, promotes more optimal use of agricultural waste, and supports the development of more efficient and sustainable livestock businesses.